Circular economy and agritourism: a sustainable behavioral model for tourists and farmers in the post-COVID era - Ingrassia, Marzia; Bacarella, Simona; Bellia, Claudio; Columba, Pietro; Adamo, Marzia Maria; Altamore, Luca; Chironi, Stefania (Frontiers in Sustainable Food Systems, 2023)
In recent years, issues related to environmental and ecosystem protection have been given greater consideration than in the past. The goal of adopting sustainable development models is vigorously pursued in the European Union and is reflected concretely in the new Common Agricultural Policy 2023-2027. The circular economy can certainly be an emerging economic response that can effectively replace growth models centered on a linear view. Agriculture and tourism are two crucial sectors where the “green transition” should be encouraged to help achieve sustainability goals through economic circularity. The Agritourism’s activity may be relevant in contributing to a behavioral change based on ethical choices. The aim of the study is to find out if Agritourisms can be the forerunners for the green transition. The objective is to know the motivations and the current level of awareness and adoption of concrete behaviors of circular economy by Agritourisms and their guests. The tourists’ preferences for Sicilian agritourism offerings were also observed. Two types of surveys were conducted: a Census of the Sicilian Agritourisms active at an on-line travel agency and a sampling survey of the Agritourism’s visitors. The results showed that Agritourism by its very nature carries the green transition, partly due to the enormous financial support of the new CAP. Second, it is a provider of quality food and ecosystem services, and a promoter of healthy behaviors and consumption of seasonal and local short-chain products by visitors, so it can be a vehicle for the adoption of the “Mediterranean Diet” as a sustainable lifestyle and food system. Tourists’ propensity to seek out environmentally friendly products and green services can help to improve for more ethical, responsible, and sustainable tourism. A sustainable behavioral model for farmers and tourists was provided.